The Development of the Basic Obstetric Ultrasound Learning Media for Undergraduate Medical Students - HERLAMBANG HERLAMBANG; AMELIA DWI FITRI; NYIMAS NATASHA AYU SHAFIRA; ELFIANI ELFIANI; ANGGELIA PUSPASARI; SUSAN TARAWIFA (Universitas Jambi, Indonesia, 2020)
Current medical education curriculum refers to the Indonesian Medical Doctor’s Standard of Competence 2012. Competencies are detailed in seven general areas of competence to be achieved by medical students. This study focused on the development of learning media in the form of guide book and video related to the basic obstetric ultrasound examination and its influence in improving student’s knowledge of basic obstetric examination skills. A quantitative method used to see the effectiveness of the learning media that we developed. Twenty-one under graduate medical students who undertook clinical rotation in the Department of Obstetrics and Gynecology participated in this study through completing the pre-post student’s questionnaires to assess the students' knowledge before and after the delivery of learning media. The collected data were analyzed with a computer program; Means and Standard Deviation were calculated as descriptive parameters. Parametric tests were used to test the hypotheses. The pre-post results were compared using the Wilcoxon statistical test. The results showed a significant difference in the score of pretest and posttest. There was an increase in the average score of pretest and posttest for students after obtaining the teaching media and clinical supervision. The value of each individual was also increased. The analysis with the Wilcoxon statistical test showed significant differences which mean that there were improvements on student’s knowledge of basic obstetric examination skills after the delivery of guide book and video. The use of teaching media in the form of basic obstetric ultrasound module and video contributed to positive results to improve the student’s knowledge.